A self-repairing sealing material for new energy vehicle tires with adhered silent cotton

By using self-healing sealing materials composed of modified polyurethane, fillers and environmentally friendly urea-formaldehyde furan on tires of new energy vehicles, and adhering high-temperature resistant silent cotton, tire noise and self-repair problems are solved, and safety and noise isolation effects are achieved under high temperature conditions.

CN118725807BActive Publication Date: 2025-03-28WUXI I REACH TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410827591.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-03-28
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The noise problem of new energy vehicle tires is prominent when driving at medium and low speeds. The existing silent cotton materials are flammable under high temperature conditions, and the high temperature resistance of self-repair glue is insufficient, so it is impossible to effectively achieve the dual effects of silent and self-repair.

Method used

A new energy vehicle tire self-repair sealing material with a silent cotton adhered to it is composed of modified polyurethane, filler and environmentally friendly urea-formaldehyde furan. The silent cotton is a high-temperature-resistant sound insulation material and is bonded to the surface of the self-repair sealing material.

Benefits of technology

It realizes the self-repair effect of not burning under high temperature conditions, while effectively blocking noise, improving the durability and comfort of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004910961250000101
    Figure BDA0004910961250000101
Patent Text Reader

Abstract

The present invention relates to the field of new energy vehicle tires, and specifically to a self-repairing sealing material for new energy vehicle tires with adhered silent cotton. The self-repairing sealing material adheres to the inner surface of the tire, and the silent cotton adheres to the surface of the self-repairing sealing material; wherein, the components of the self-repairing sealing material include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan; wherein, the mass ratio of modified polyurethane, filler and environmentally friendly urea-formaldehyde furan is 7.2-8.5:0.3-0.8:1.2-2. Among them, the modified polyurethane is modified by adding a modifier during the synthesis process of the existing polyurethane, the filler is inorganic particles, and the environmentally friendly urea-formaldehyde furan is used as an auxiliary additive. The modified polyurethane has good high temperature resistance and self-repairing properties. In addition, high temperature resistant silent cotton is also adhered to the surface of the self-repairing sealing material to ensure that it will not burn under high temperature conditions, and it can also play a role in blocking noise while completing self-repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new energy vehicle tires, and in particular to a new energy vehicle tire self-repairing sealing material with adhered silent cotton. Background Art

[0002] Currently, new energy vehicles, including electric vehicles and hybrid vehicles, generally rely on quieter electric drives for low and medium speed driving. However, after the noise of the power system is reduced, the noise problem of the tire becomes more obvious. The noise of the tire comes from three aspects, namely, carcass noise, pattern noise, and cavity resonance noise: (1) Carcass noise is the periodic noise vibration caused by the high-frequency collision between the carcass and the ground. At present, most low-end cars use tires with harder treads, and the carcass noise will be very obvious. Therefore, many tire manufacturers will choose to soften the rubber formula to reduce carcass noise, but this will actually reduce the durability of the tire. (2) Pattern noise is the air noise caused by the air flow in the gap between the tire patterns and the air disturbance around the tire. Therefore, many tire manufacturers will design more detailed patterns to reduce the pattern noise caused by the pumping effect, but this will reduce the tire's grip and drainage performance. (3) Cavity resonance noise is like the noise generated when hitting a basketball. The inside of the tire is a cavity, and the movement of this cavity will also generate noise. However, there is a lack of effective means to reduce cavity resonance from the tire itself. The silent cotton tire is a new technical approach to solve tire noise, which can solve the resonance of the tire body, pattern, and cavity, and make up for the derivative problems caused by the above methods. Therefore, with the popularization of new energy vehicles, silent cotton tires have also been frequently mentioned in recent years.

[0003] In order to make the driving experience more comfortable and quiet, many new energy vehicle tires are very concerned about the research and development of silent cotton technology. However, not all tires can be silent by sticking a layer of so-called "silent cotton". The silent effect of directly installing silent cotton on ordinary tires is not so obvious. In addition, in order to improve the repairability of new energy vehicle tires, some companies have begun to study self-sealing liquid glue, combining self-sealing glue with silent cotton and coating it on the surface of automobile tires. In theory, it will achieve the dual effects of self-repair and silence, but the actual situation is that high temperature will be generated inside the tire during rolling. Ordinary silent cotton is not heat-resistant, so it may spontaneously combust as the temperature rises, and the high temperature resistance of ordinary self-repair glue is also poor. Therefore, not only can the effect of silence and repair not be achieved, but it will pose a greater threat to personal safety. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a new energy vehicle tire self-repair sealing material with adhered silent cotton.

[0005] The purpose of the present invention is achieved by adopting the following technical solutions:

[0006] A new energy vehicle tire self-repairing sealing material with adhered silent cotton, wherein the self-repairing sealing material is adhered to the inner surface of the tire, and the silent cotton is bonded to the surface of the self-repairing sealing material;

[0007] Among them, the components of the self-repairing sealing material include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan; among them, the mass ratio of modified polyurethane, filler and environmentally friendly urea-formaldehyde furan is 7.2~8.5:0.3~0.8:1.2~2.

[0008] Preferably, the sound-proof cotton is a high-temperature resistant sound-insulating material, and its components include at least one of slag wool, rock wool, aluminum silicate wool, ceramic fiber wool, and polyurethane wool.

[0009] Preferably, the side of the noise-reducing cotton away from the self-repairing sealing material has a wavy or flat structure, so as to have a larger surface area to absorb the noise generated by tire friction.

[0010] Preferably, the thickness of the self-repairing sealing material is 1 to 10 mm, and the thickness of the sound insulation cotton is 3 to 20 mm.

[0011] Preferably, the filler has a particle size of 250 to 500 nm and includes at least one of white carbon black, calcium carbonate, graphene oxide and activated carbon.

[0012] Preferably, the modified polyurethane is a product obtained by using a modifier to participate in the synthesis of polyurethane.

[0013] Preferably, the preparation method of the modifier comprises:

[0014] S1. Weigh 4,4'-diaminostilbene-2,2'-disulfonic acid and mix it in N,N-dimethylacetamide, add sodium hydroxide solution dropwise until the pH of the reaction solution is 6.0-7.0, and stir evenly at room temperature to form a mixed solution C; wherein the mass ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid to N,N-dimethylacetamide is 0.93-1.85:10; the sodium hydroxide solution is a solution of sodium hydroxide in N,N-dimethylacetamide, and the concentration of the sodium hydroxide solution is 0.01-0.05 mol / L;

[0015] S2, weigh 4-mercaptopyridine and mix it in N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution D; wherein the mass ratio of 4-mercaptopyridine to N,N-dimethylacetamide is 1.1-2.2:10;

[0016] S3. Mix the mixed solution C and the mixed solution D, add dimethyl benzoate at the same time, stir and mix for 0.5 to 1 hour under ultraviolet light, remove the solvent, purify and dry to obtain a modifier; wherein the mass ratio of the mixed solution C to the mixed solution D is 1:1.2 to 1.6; and the amount of dimethyl benzoate added is 0.1% to 0.4% of the mass of the mixed solution C.

[0017] Preferably, the preparation method of the modified polyurethane comprises:

[0018] S4, weigh hexamethylene diisocyanate and dibutyltin dilaurate, mix them in a reaction container, introduce inert gas as protective gas, and stir them thoroughly to form a mixed solution E; wherein the amount of dibutyltin dilaurate added is 0.2% to 0.5% of the hexamethylene diisocyanate;

[0019] Weigh polytetrahydrofuran and add it into N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution F; wherein the mass ratio of polytetrahydrofuran to N,N-dimethylacetamide is 1:1.5-2;

[0020] S5, placing the reaction container containing the mixed solution E in a water bath at 75-85°C, and then adding the mixed solution F dropwise. After the dropwise addition is completed, the mixture is kept warm for 3-4 hours to form a mixed reaction solution G; wherein the mass ratio of the mixed solution E to the mixed solution F is 2.2-3.2:10;

[0021] S6, mixing the modifier and 1,4-butanediol in N,N-dimethylacetamide, stirring and mixing evenly to form a mixed solution H; wherein the mass ratio of the modifier, 1,4-butanediol and N,N-dimethylacetamide is 1:0.52-0.76:10-20;

[0022] Add the mixed solution H dropwise into the mixed reaction solution G, and keep the mixture warm for 3 to 5 hours to obtain a mixed reaction solution J; wherein the mass ratio of the mixed solution H to the mixed reaction solution G is 1:2 to 4;

[0023] S7. Place the mixed reaction liquid J into a mold and place it at 85-98° C. for 18-24 hours. Then take the product out of the molding mold, crush it, and dry it under vacuum for 10-15 hours to finally obtain the modified polyurethane.

[0024] Preferably, the preparation method of the environmentally friendly urea-formaldehyde furan comprises:

[0025] P1. Weigh terephthalaldehyde and deionized water, mix them, then heat them to 85-95°C, add sodium hydroxide solution dropwise until the pH is 9.0-9.5, and obtain a mixed solution A; wherein the concentration of the sodium hydroxide solution is 0.05-0.1 mol / L; and the mass ratio of terephthalaldehyde to deionized water is 1.3-1.8:10;

[0026] P2. Weigh urea and dissolve it in deionized water, then gradually add it to the mixed solution A at a dropping speed of 1 to 2 seconds per drop. After the dropping is completed, the reaction system is heated to 95 to 100°C and refluxed for 1 to 2 hours to obtain a mixed solution B; wherein the mass ratio of urea to deionized water is 0.6 to 1:10;

[0027] P3. After the mixed solution B is cooled to 45-55°C, furfuryl alcohol solution is added, and after sufficient stirring, the pH is adjusted to 4.5-5.5, and the temperature is continued to be raised to 100°C, and the reaction is kept warm for 2-4 hours. After the reaction is completed, the temperature is lowered to 70-75°C, and the pH is adjusted to 7-7.5. After removing the solvent, it is dried to obtain urea-formaldehyde furan; wherein the furfuryl alcohol solution is furfuryl alcohol and deionized water in a mass ratio of 2-3.2:10, and the mass ratio of the furfuryl alcohol solution to the mixed solution B is 1:0.42-0.58.

[0028] Preferably, during the use of the new energy vehicle tire self-repairing sealing material with adhered silent cotton, the modified polyurethane, filler and environmentally friendly urea-formaldehyde furan are first weighed according to the mass ratio and mixed in anhydrous ethanol, and then fully stirred to form a self-repairing liquid, which is applied to the inner surface of the automobile tire. At the same time, the silent cotton is attached to the coated self-repairing liquid. After drying at room temperature for at least 24 hours, the new energy vehicle tire self-repairing sealing material with adhered silent cotton is obtained.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present invention discloses a self-repairing sealing material for new energy vehicle tires with adhered silent cotton, the components of which include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan. Among them, the modified polyurethane is modified by adding a modifier during the synthesis process of the existing polyurethane, the filler is inorganic particles, and the environmentally friendly urea-formaldehyde furan is used as an auxiliary additive. The self-repairing sealing material prepared by the present invention has good high temperature resistance and self-repairing properties. In addition, high-temperature resistant silent cotton is adhered to the surface of the self-repairing sealing material to ensure that it will not burn under high temperature conditions, and it can also play a role in blocking noise while completing self-repair.

[0031] 2. The modified polyurethane material is obtained by using the modifier prepared by the present invention to participate in the synthesis process of polyurethane. Among them, the modifier is prepared by using an active compound containing both diamino and vinyl groups (4,4'-diaminostilbene-2,2'-disulfonic acid) and a pyridine containing a thiol group (4-mercaptopyridine) through click reactions. The preparation process of the modifier utilizes the combination of thiol and vinyl, and the product obtained is a diamino compound containing both a thioester bond and a pyridine group. The modifier compound is introduced into the polyurethane material, and the modified polyurethane formed has better thermal stability and self-healing properties, as well as better improvements in mechanical properties.

[0032] 3. In the present invention, the environmentally friendly urea-formaldehyde furan is prepared by replacing the traditional formaldehyde in the reaction with terephthalaldehyde, and the reaction conditions are appropriately changed during the reaction. The final product urea-formaldehyde furan is not only more environmentally friendly, but also has improved high temperature resistance and acid and alkali resistance, and is not easy to decompose. After being used in combination with modified polyurethane, the compatibility of the mixture is better than that of conventional urea-formaldehyde furan. DETAILED DESCRIPTION

[0033] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0034] The present invention will be further described below in conjunction with the following examples.

[0035] Example 1

[0036] A self-repairing sealing material for new energy vehicle tires with adhered silent cotton, wherein the self-repairing sealing material is adhered to the inner surface of the tire, and the silent cotton is bonded to the surface of the self-repairing sealing material; the silent cotton is a high-temperature resistant sound insulation material, the thickness of the sound insulation cotton is 15 mm, and the composition is aluminum silicate wool; the side of the silent cotton away from the self-repairing sealing material is a corrugated structure, the purpose of which is to have a larger surface area to absorb the noise generated by tire friction.

[0037] Among them, the components of the self-repairing sealing material include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan, and the thickness of the self-repairing sealing material is 5mm; among them, the mass ratio of modified polyurethane, filler and environmentally friendly urea-formaldehyde furan is 7.8:0.5:1.6; the filler is white carbon black, and the particle size is 250-500nm.

[0038] The preparation method of modified polyurethane comprises:

[0039] S1. Weigh 4,4'-diaminostilbene-2,2'-disulfonic acid and mix it in N,N-dimethylacetamide, add sodium hydroxide solution dropwise until the pH of the reaction solution is 6.0-7.0, and stir evenly at room temperature to form a mixed solution C; wherein the mass ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid to N,N-dimethylacetamide is 1.4:10; the sodium hydroxide solution is a solution of sodium hydroxide in N,N-dimethylacetamide, and the concentration of the sodium hydroxide solution is 0.03 mol / L;

[0040] S2, weigh 4-mercaptopyridine and mix it in N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution D; wherein the mass ratio of 4-mercaptopyridine to N,N-dimethylacetamide is 1.65:10;

[0041] S3, mixing the mixed solution C with the mixed solution D, adding dimethyl benzoate at the same time, stirring and mixing for 1 hour under ultraviolet light, removing the solvent, purifying and drying to obtain a modifier; wherein the mass ratio of the mixed solution C to the mixed solution D is 1:1.4; the amount of dimethyl benzoate added is 0.3% of the mass of the mixed solution C;

[0042] S4, weigh hexamethylene diisocyanate and dibutyltin dilaurate, mix them in a reaction container, introduce inert gas as protective gas, and stir them thoroughly to form a mixed solution E; wherein the amount of dibutyltin dilaurate added is 0.4% of hexamethylene diisocyanate;

[0043] Weigh polytetrahydrofuran and add it to N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution F; wherein the mass ratio of polytetrahydrofuran to N,N-dimethylacetamide is 1:1.8;

[0044] S5, placing the reaction container containing the mixed solution E in a water bath at 80°C, and then adding the mixed solution F dropwise. After the addition is completed, the mixture is kept warm for 3.5 hours to form a mixed reaction solution G; wherein the mass ratio of the mixed solution E to the mixed solution F is 2.7:10;

[0045] S6, mixing the modifier and 1,4-butanediol in N,N-dimethylacetamide, stirring and mixing evenly to form a mixed solution H; wherein the mass ratio of the modifier, 1,4-butanediol and N,N-dimethylacetamide is 1:0.65:15;

[0046] The mixed solution H was added dropwise into the mixed reaction solution G, and the mixture was kept warm for 4 hours to obtain a mixed reaction solution J; wherein the mass ratio of the mixed solution H to the mixed reaction solution G was 1:3;

[0047] S7. Place the mixed reaction liquid J in a mold and place it at 95° C. for 20 hours. Then take the product out of the molding mold, crush it, and dry it under vacuum for 12 hours to finally obtain the modified polyurethane.

[0048] The preparation method of environmentally friendly urea-formaldehyde furan comprises:

[0049] P1. Weigh terephthalaldehyde and deionized water, mix them, then heat them to 90°C, add sodium hydroxide solution dropwise until the pH is 9.0-9.5, and obtain a mixed solution A; wherein the concentration of the sodium hydroxide solution is 0.06 mol / L; and the mass ratio of terephthalaldehyde to deionized water is 1.5:10;

[0050] P2. Weigh urea and dissolve it in deionized water, then gradually add it to the mixed solution A at a dropping speed of 1.5 seconds / drop. After the addition is completed, the reaction system is heated to 100° C. and refluxed for 1.5 hours to obtain a mixed solution B; wherein the mass ratio of urea to deionized water is 0.8:10;

[0051] P3. After the mixed solution B is cooled to 50°C, furfuryl alcohol solution is added, and after sufficient stirring, the pH is adjusted to 4.5-5.5, and the temperature is continued to be raised to 100°C, and the reaction is kept warm for 3 hours. After the reaction is completed, the temperature is lowered to 70°C, and the pH is adjusted to 7-7.5. After removing the solvent, it is dried to obtain urea-formaldehyde furan; wherein the furfuryl alcohol solution is furfuryl alcohol and deionized water in a mass ratio of 2.6:10, and the mass ratio of the furfuryl alcohol solution to the mixed solution B is 1:0.52.

[0052] The preparation of the self-repairing sealing material of the new energy vehicle tire with the silent cotton adhered thereto includes:

[0053] During use, first weigh the modified polyurethane, filler and environmentally friendly urea-formaldehyde furan according to the mass ratio and mix them in anhydrous ethanol. After fully stirring, a self-repairing liquid is formed and applied to the inner surface of the car tire. At the same time, the sound-proof cotton is attached to the coated self-repairing liquid. After drying at room temperature for 24 hours, a new energy vehicle tire self-repairing sealing material with sound-proof cotton adhered to it is obtained.

[0054] Example 2

[0055] A self-repairing sealing material for new energy vehicle tires with adhered silent cotton, wherein the self-repairing sealing material is adhered to the inner surface of the tire, and the silent cotton is bonded to the surface of the self-repairing sealing material; the silent cotton is a high-temperature resistant sound insulation material, the thickness of the sound insulation cotton is 3 to 20 mm, and the composition is ceramic fiber cotton; the side of the silent cotton away from the self-repairing sealing material is a corrugated structure, the purpose of which is to have a larger surface area to absorb the noise generated by tire friction.

[0056] Among them, the components of the self-repairing sealing material include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan, and the thickness of the self-repairing sealing material is 1 mm; among them, the mass ratio of modified polyurethane, filler and environmentally friendly urea-formaldehyde furan is 7.2:0.3:1.2.

[0057] The filler is calcium carbonate with a particle size of 250 to 500 nm.

[0058] The preparation method of modified polyurethane comprises:

[0059] S1. Weigh 4,4'-diaminostilbene-2,2'-disulfonic acid and mix it in N,N-dimethylacetamide, add sodium hydroxide solution dropwise until the pH of the reaction solution is 6.0-7.0, and stir evenly at room temperature to form a mixed solution C; wherein the mass ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid to N,N-dimethylacetamide is 0.93:10; the sodium hydroxide solution is a solution of sodium hydroxide in N,N-dimethylacetamide, and the concentration of the sodium hydroxide solution is 0.01 mol / L;

[0060] S2, weigh 4-mercaptopyridine and mix it in N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution D; wherein the mass ratio of 4-mercaptopyridine to N,N-dimethylacetamide is 1.1:10;

[0061] S3, mixing the mixed solution C with the mixed solution D, adding dimethyl benzoate at the same time, stirring and mixing for 0.5h under ultraviolet light, removing the solvent, purifying and drying to obtain a modifier; wherein the mass ratio of the mixed solution C to the mixed solution D is 1:1.2; the amount of dimethyl benzoate added is 0.1% of the mass of the mixed solution C;

[0062] S4, weigh hexamethylene diisocyanate and dibutyltin dilaurate, mix them in a reaction container, introduce inert gas as protective gas, and stir them thoroughly to form a mixed solution E; wherein the amount of dibutyltin dilaurate added is 0.2% of the hexamethylene diisocyanate;

[0063] Weigh polytetrahydrofuran and add it to N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution F; wherein the mass ratio of polytetrahydrofuran to N,N-dimethylacetamide is 1:1.5;

[0064] S5, placing the reaction container containing the mixed solution E in a 75°C water bath, and then adding the mixed solution F dropwise. After the dropwise addition is completed, the mixture is kept warm for 3 hours to form a mixed reaction solution G; wherein the mass ratio of the mixed solution E to the mixed solution F is 2.2:10;

[0065] S6, mixing the modifier and 1,4-butanediol in N,N-dimethylacetamide, stirring and mixing evenly to form a mixed solution H; wherein the mass ratio of the modifier, 1,4-butanediol and N,N-dimethylacetamide is 1:0.52:10;

[0066] Add the mixed solution H dropwise into the mixed reaction solution G, and keep the mixture warm for 3 to 5 hours to obtain a mixed reaction solution J; wherein the mass ratio of the mixed solution H to the mixed reaction solution G is 1:2;

[0067] S7. Place the mixed reaction liquid J in a mold and place it at 85° C. for 18 hours. Then take the product out of the molding mold, crush it, and dry it under vacuum for 10 hours to finally obtain the modified polyurethane.

[0068] The preparation method of environmentally friendly urea-formaldehyde furan comprises:

[0069] P1. Weigh terephthalaldehyde and deionized water, mix them, then heat them to 85°C, add sodium hydroxide solution dropwise until the pH is 9.0-9.5, and obtain a mixed solution A; wherein the concentration of the sodium hydroxide solution is 0.05 mol / L; and the mass ratio of terephthalaldehyde to deionized water is 1.3:10;

[0070] P2. Weigh urea and dissolve it in deionized water, then gradually add it to the mixed solution A at a dropping speed of 1 to 2 seconds per drop. After the addition is completed, the reaction system is heated to 95° C. and refluxed for 1 hour to obtain a mixed solution B; wherein the mass ratio of urea to deionized water is 0.6:10;

[0071] P3. After the mixed solution B is cooled to 45°C, furfuryl alcohol solution is added, and after sufficient stirring, the pH is adjusted to 4.5-5.5, and the temperature is continued to be raised to 100°C, and the reaction is kept warm for 2 hours. After the reaction is completed, the temperature is lowered to 70°C, and the pH is adjusted to 7-7.5. After removing the solvent, it is dried to obtain urea-formaldehyde furan; wherein the furfuryl alcohol solution is furfuryl alcohol and deionized water in a mass ratio of 2:10, and the mass ratio of the furfuryl alcohol solution to the mixed solution B is 1:0.42.

[0072] The preparation of the self-repairing sealing material of the new energy vehicle tire with the silent cotton adhered thereto includes:

[0073] During use, first weigh the modified polyurethane, filler and environmentally friendly urea-formaldehyde furan according to the mass ratio and mix them in anhydrous ethanol. After fully stirring, a self-repairing liquid is formed and applied to the inner surface of the automobile tire. At the same time, the sound-proof cotton is attached to the coated self-repairing liquid. After drying at room temperature for at least 24 hours, a new energy vehicle tire self-repairing sealing material with sound-proof cotton adhered thereto is obtained.

[0074] Example 3

[0075] A self-repairing sealing material for new energy vehicle tires with adhered silent cotton, wherein the self-repairing sealing material is adhered to the inner surface of the tire, and the silent cotton is bonded to the surface of the self-repairing sealing material; the silent cotton is a high-temperature resistant sound insulation material, the thickness of the sound insulation cotton is 20 mm, and the component is rock wool; the side of the silent cotton away from the self-repairing sealing material is a corrugated structure, the purpose of which is to have a larger surface area to absorb the noise generated by tire friction.

[0076] Among them, the components of the self-repairing sealing material include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan, and the thickness of the self-repairing sealing material is 10mm; among them, the mass ratio of modified polyurethane, filler and environmentally friendly urea-formaldehyde furan is 8.5:0.8:2.

[0077] The filler is activated carbon with a particle size of 250 to 500 nm.

[0078] The preparation method of modified polyurethane comprises:

[0079] S1. Weigh 4,4'-diaminostilbene-2,2'-disulfonic acid and mix it in N,N-dimethylacetamide, add sodium hydroxide solution dropwise until the pH of the reaction solution is 6.0-7.0, and stir evenly at room temperature to form a mixed solution C; wherein the mass ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid to N,N-dimethylacetamide is 1.85:10; the sodium hydroxide solution is a solution of sodium hydroxide in N,N-dimethylacetamide, and the concentration of the sodium hydroxide solution is 0.05 mol / L;

[0080] S2, weigh 4-mercaptopyridine and mix it in N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution D; wherein the mass ratio of 4-mercaptopyridine to N,N-dimethylacetamide is 2.2:10;

[0081] S3, mixing the mixed solution C with the mixed solution D, adding benzoin dimethyl ether at the same time, stirring and mixing for 0.5 to 1 hour under ultraviolet light, removing the solvent, purifying and drying to obtain a modifier; wherein the mass ratio of the mixed solution C to the mixed solution D is 1:1.6; the amount of benzoin dimethyl ether added is 0.4% of the mass of the mixed solution C;

[0082] S4, weigh hexamethylene diisocyanate and dibutyltin dilaurate, mix them in a reaction container, introduce inert gas as protective gas, and stir them thoroughly to form a mixed solution E; wherein the amount of dibutyltin dilaurate added is 0.5% of the hexamethylene diisocyanate;

[0083] Weigh polytetrahydrofuran and add it to N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution F; wherein the mass ratio of polytetrahydrofuran to N,N-dimethylacetamide is 1:2;

[0084] S5, placing the reaction container containing the mixed solution E in a water bath at 85°C, and then adding the mixed solution F dropwise. After the dropwise addition is completed, the mixture is kept warm for 4 hours to form a mixed reaction solution G; wherein the mass ratio of the mixed solution E to the mixed solution F is 3.2:10;

[0085] S6, mixing the modifier and 1,4-butanediol in N,N-dimethylacetamide, stirring and mixing evenly to form a mixed solution H; wherein the mass ratio of the modifier, 1,4-butanediol and N,N-dimethylacetamide is 1:0.76:20;

[0086] The mixed solution H was added dropwise into the mixed reaction solution G, and the mixture was kept warm for 5 hours to obtain a mixed reaction solution J; wherein the mass ratio of the mixed solution H to the mixed reaction solution G was 1:4;

[0087] S7. Place the mixed reaction liquid J in a mold and place it at 98° C. for 24 hours. Then take the product out of the molding mold, crush it, and dry it under vacuum for 15 hours to finally obtain modified polyurethane.

[0088] The preparation method of environmentally friendly urea-formaldehyde furan comprises:

[0089] P1. Weigh terephthalaldehyde and deionized water, mix them, then heat them to 95°C, add sodium hydroxide solution dropwise until the pH is 9.0-9.5, and obtain a mixed solution A; wherein the concentration of the sodium hydroxide solution is 0.1 mol / L; and the mass ratio of terephthalaldehyde to deionized water is 1.8:10;

[0090] P2. Weigh urea and dissolve it in deionized water, then gradually add it to the mixed solution A at a dropping speed of 2 seconds / drop. After the dropping is completed, the reaction system is heated to 100°C and refluxed for 2 hours to obtain a mixed solution B; wherein the mass ratio of urea to deionized water is 1:10;

[0091] P3. After the mixed solution B is cooled to 55°C, furfuryl alcohol solution is added, and after sufficient stirring, the pH is adjusted to 4.5-5.5, and the temperature is continued to be raised to 100°C, and the reaction is kept warm for 4 hours. After the reaction is completed, the temperature is lowered to 75°C, and the pH is adjusted to 7-7.5. After removing the solvent, it is dried to obtain urea-formaldehyde furan; wherein the furfuryl alcohol solution is furfuryl alcohol and deionized water in a mass ratio of 3.2:10, and the mass ratio of the furfuryl alcohol solution to the mixed solution B is 1:0.58.

[0092] The preparation of the self-repairing sealing material of the new energy vehicle tire with the silent cotton adhered thereto includes:

[0093] During use, first weigh the modified polyurethane, filler and environmentally friendly urea-formaldehyde furan according to the mass ratio and mix them in anhydrous ethanol. After fully stirring, a self-repairing liquid is formed and applied to the inner surface of the automobile tire. At the same time, the sound-proof cotton is attached to the coated self-repairing liquid. After drying at room temperature for at least 24 hours, a new energy vehicle tire self-repairing sealing material with sound-proof cotton adhered thereto is obtained.

[0094] Comparative Example 1

[0095] A new energy vehicle tire self-repairing sealing material with adhered silent cotton, which differs from Example 1 in that the modified polyurethane in the self-repairing sealing material component is replaced with ordinary polyurethane, that is, polyurethane without adding a modifier.

[0096] The self-repairing sealing material comprises polyurethane, filler and environmentally friendly urea-formaldehyde furan, and the thickness of the self-repairing sealing material is 5 mm; wherein the mass ratio of polyurethane, filler and environmentally friendly urea-formaldehyde furan is 7.8:0.5:1.6; the filler is white carbon black, and the particle size is 250-500 nm. The preparation process of environmentally friendly urea-formaldehyde furan is the same as that of Example 1.

[0097] The preparation method of polyurethane comprises:

[0098] S1. Weigh hexamethylene diisocyanate and dibutyltin dilaurate, mix them in a reaction container, introduce an inert gas as a protective gas, and stir them thoroughly to form a mixed solution A; wherein the amount of dibutyltin dilaurate added is 0.5% of the hexamethylene diisocyanate;

[0099] Weigh polytetrahydrofuran and add it to N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution B; wherein the mass ratio of polytetrahydrofuran to N,N-dimethylacetamide is 1:2;

[0100] S2, placing the reaction container containing the mixed solution A in a water bath at 85°C, and then adding the mixed solution B dropwise. After the dropwise addition is completed, the mixture is kept warm for 4 hours to form a mixed reaction solution C; wherein the mass ratio of the mixed solution A to the mixed solution B is 3.2:10;

[0101] S3. Place the mixed reaction liquid C in a mold and place it at 98° C. for 24 hours. Then take the product out of the molding mold, crush it, and dry it under vacuum for 15 hours to finally obtain polyurethane.

[0102] Comparative Example 2

[0103] A new energy vehicle tire self-repairing sealing material with adhered silent cotton, which differs from Example 1 in that the environmentally friendly urea-formaldehyde furan in the self-repairing sealing material components is replaced with conventional urea-formaldehyde furan.

[0104] The self-repairing sealing material comprises modified polyurethane, filler and urea-formaldehyde furan, and the thickness of the self-repairing sealing material is 5 mm; wherein the mass ratio of modified polyurethane, filler and urea-formaldehyde furan is 7.8:0.5:1.6; the filler is white carbon black, and the particle size is 250-500 nm. The preparation process of the modified polyurethane is the same as that of Example 1.

[0105] The preparation method of urea-formaldehyde furan comprises:

[0106] P1. Weigh formaldehyde and deionized water, mix them, and then heat them to 90°C. After they are completely dissolved, add sodium hydroxide solution dropwise until the pH is 9.0-9.5 to obtain a mixed solution A; wherein the concentration of the sodium hydroxide solution is 0.06 mol / L; and the mass ratio of formaldehyde to deionized water is 1.5:10;

[0107] P2. Weigh urea and dissolve it in deionized water, then gradually add it to the mixed solution A at a dropping speed of 1.5 seconds / drop. After the addition is completed, the reaction system is heated to 100° C. and refluxed for 1.5 hours to obtain a mixed solution B; wherein the mass ratio of urea to deionized water is 0.8:10;

[0108] P3. After the mixed solution B is cooled to 50°C, furfuryl alcohol solution is added, and after sufficient stirring, the pH is adjusted to 4.5-5.5, and the temperature is continued to be raised to 100°C, and the reaction is kept warm for 3 hours. After the reaction is completed, the temperature is lowered to 70°C, and the pH is adjusted to 7-7.5. After removing the solvent, it is dried to obtain urea-formaldehyde furan; wherein the furfuryl alcohol solution is furfuryl alcohol and deionized water in a mass ratio of 2.6:10, and the mass ratio of the furfuryl alcohol solution to the mixed solution B is 1:0.52.

[0109] Comparative Example 3

[0110] A new energy vehicle tire self-repairing sealing material with adhered silent cotton, which differs from Example 1 in that the modified polyurethane in the self-repairing sealing material component is replaced by ordinary polyurethane, and the environmentally friendly urea-formaldehyde furan is replaced by ordinary urea-formaldehyde furan.

[0111] The self-repairing sealing material comprises polyurethane, filler and urea-formaldehyde furan, and the thickness of the self-repairing sealing material is 5 mm; wherein the mass ratio of polyurethane, filler and urea-formaldehyde furan is 7.8:0.5:1.6; the filler is white carbon black, and the particle size is 250-500 nm. The preparation method of polyurethane is the same as that of comparative example 1, and the preparation method of urea-formaldehyde furan is the same as that of comparative example 2.

[0112] In order to make the content of the present invention clearer, the self-repairing sealing materials obtained in Example 1 and Comparative Examples 1-3 were tested for performance. The mechanical test was based on GB / T2941, and the bonding force was based on GB / T 30774. The results are shown in Table 1:

[0113] Table 1 Performance of different self-healing materials

[0114]

[0115]

[0116] It can be seen from Table 1 that the tensile strength and elongation at break of the self-repairing sealing material prepared in Example 1 of the present invention are higher, and the high temperature resistance exceeds 135°C. The room temperature bonding force with rubber is as high as 693N / m. Even after high temperature treatment (aging at 100°C for 12h), the bonding force can still be maintained at 675N / m, which is not achievable in the comparative example. In addition, the sealing material of Example 1 can achieve a repair rate of 83.2% after self-repairing for 20h at room temperature, and a repair rate of 94.1% after self-repairing for 10h at a high temperature of 80°C, indicating that the self-repairing effect is very good and the repair performance is also better at higher temperatures; while the repair rate in the comparative example cannot reach the effect of Example 1, the possible reason is that the high temperature resistance and stability are poor, resulting in poor repair effect.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A new energy vehicle tire self-repair sealing material with adhered silent cotton, characterized in that: The self-repairing sealing material is adhered to the inner surface of the tire, and the silent cotton is adhered to the surface of the self-repairing sealing material; The components of the self-repairing sealing material include modified polyurethane, filler and environmentally friendly urea-formaldehyde furan; wherein the mass ratio of the modified polyurethane, filler and environmentally friendly urea-formaldehyde furan is 7.2~8.5:0.3~0.8:1.2~2; The modified polyurethane is a product obtained by using a modifier to participate in the synthesis of polyurethane; The preparation method of the modifier comprises: S1. Weigh 4,4'-diaminostilbene-2,2'-disulfonic acid and mix it in N,N-dimethylacetamide, add sodium hydroxide solution dropwise until the pH of the reaction solution is 6.0-7.0, and stir evenly at room temperature to form a mixed solution C; wherein the mass ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid to N,N-dimethylacetamide is 0.93-1.85:10; the sodium hydroxide solution is a solution of sodium hydroxide in N,N-dimethylacetamide, and the concentration of the sodium hydroxide solution is 0.01-0.05 mol / L; S2, weigh 4-mercaptopyridine and mix it in N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution D; wherein the mass ratio of 4-mercaptopyridine to N,N-dimethylacetamide is 1.1-2.2:10; S3, mixing the mixed solution C with the mixed solution D, adding benzoin dimethyl ether at the same time, stirring and mixing for 0.5 to 1 hour under ultraviolet light, removing the solvent, purifying and drying to obtain a modifier; wherein the mass ratio of the mixed solution C to the mixed solution D is 1:1.2 to 1.6; the amount of benzoin dimethyl ether added is 0.1% to 0.4% of the mass of the mixed solution C; The preparation method of the modified polyurethane comprises: S4, weigh hexamethylene diisocyanate and dibutyltin dilaurate, mix them in a reaction container, introduce inert gas as protective gas, and stir them thoroughly to form a mixed solution E; wherein the amount of dibutyltin dilaurate added is 0.2% to 0.5% of the hexamethylene diisocyanate; Weigh polytetrahydrofuran and add it to N,N-dimethylacetamide, and mix them thoroughly to obtain a mixed solution F; wherein the mass ratio of polytetrahydrofuran to N,N-dimethylacetamide is 1:1.5-2; S5, placing the reaction container containing the mixed solution E in a water bath at 75-85°C, and then adding the mixed solution F dropwise. After the addition is completed, heat-retaining the reaction for 3-4 hours to form a mixed reaction solution G; wherein the mass ratio of the mixed solution E to the mixed solution F is 2.2-3.2:10; S6, mixing the modifier and 1,4-butanediol in N,N-dimethylacetamide, stirring and mixing evenly to form a mixed solution H; wherein the mass ratio of the modifier, 1,4-butanediol and N,N-dimethylacetamide is 1:0.52~0.76:10~20; Add the mixed solution H dropwise into the mixed reaction solution G, and keep the mixture warm for 3-5 hours to obtain a mixed reaction solution J; wherein the mass ratio of the mixed solution H to the mixed reaction solution G is 1:2-4; S7, placing the mixed reaction liquid J in a mold, placing it at 85-98° C. for 18-24 hours, then taking the product out of the molding mold, crushing it, and drying it under vacuum for 10-15 hours to finally obtain a modified polyurethane; The preparation method of the environmentally friendly urea-formaldehyde furan comprises: P1. Weigh terephthalaldehyde and deionized water, mix them, then heat them to 85-95°C, add sodium hydroxide solution dropwise until the pH is 9.0-9.5, and obtain a mixed solution A; wherein the concentration of the sodium hydroxide solution is 0.05-0.1 mol / L; and the mass ratio of terephthalaldehyde to deionized water is 1.3-1.8:10; P2. Weigh urea and dissolve it in deionized water, then gradually add it to the mixed solution A at a dropping speed of 1-2 seconds / drop. After the dropping is completed, the reaction system is heated to 95-100°C and refluxed for 1-2 hours to obtain a mixed solution B; wherein the mass ratio of urea to deionized water is 0.6-1:10; P3. After the mixed solution B is cooled to 45-55°C, furfuryl alcohol solution is added, and after sufficient stirring, the pH is adjusted to 4.5-5.5, and the temperature is continued to rise to 100°C, and the reaction is kept warm for 2-4 hours. After the reaction is completed, the temperature is lowered to 70-75°C, and the pH is adjusted to 7-7.

5. After removing the solvent, it is dried to obtain urea-formaldehyde furan; wherein the furfuryl alcohol solution is furfuryl alcohol and deionized water in a mass ratio of 2-3.2:10, and the mass ratio of the furfuryl alcohol solution to the mixed solution B is 1:0.42-0.

58.

2. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: The components of the sound-proof cotton include at least one of slag wool, rock wool, aluminum silicate wool, ceramic fiber wool, and polyurethane wool.

3. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: The side of the noise-reducing cotton away from the self-repairing sealing material is a wavy or flat structure.

4. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: The thickness of the self-repairing sealing material is 1-10 mm, and the thickness of the sound-proof cotton is 3-20 mm.

5. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: The filler has a particle size of 250-500 nm and includes at least one of white carbon black, calcium carbonate, graphene oxide and activated carbon.

6. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: During the use of the new energy vehicle tire self-repairing sealing material with adhered silent cotton, firstly, the modified polyurethane, filler and environmentally friendly urea-formaldehyde furan are weighed according to the mass ratio and mixed in anhydrous ethanol, and then fully stirred to form a self-repairing liquid, which is then coated on the inner surface of the automobile tire. At the same time, the silent cotton is attached to the coated self-repairing liquid. After drying at room temperature for at least 24 hours, the new energy vehicle tire self-repairing sealing material with adhered silent cotton is obtained.

Citation Information

Patent Citations

  • Repairable mute tire

    CN110395076A

  • Thermoplastic elastomer super-wear-resistant mute material and preparation method thereof

    CN117343528A